Protective role of Astragaloside IV in chronic glomerulonephritis by activating autophagy through PI3K/AKT/AS160 pathway. (29th July 2020) - Lu, Ruirui; Chen, Junqi; Liu, Bihao; Lin, Hua; Bai, Lixia; Zhang, Peichun; Chen, Dandan; Li, Honglian; Li, Jicheng; Pang, Yu; Zhou, Yuan; Zhou, Jiuyao; et al.
Abstract : Astragaloside IV(AS‐IV), a saponin purified from Astragalus membranaceus ( Fisch .) Bge.var.mongholicus (Bge.) Hsiao, has been widely used in traditional Chinese medicine. However, the underlying mechanisms in treating chronic glomerular nephritis (CGN) have not been fully understood. The aim of the present study was to evaluate the potential mechanism of AS‐IV on CGN. CGN rats were administrated with AS‐IV at 10 mg·kg −1 ·d −1 (ASL) and 20 mg·kg −1 ·d −1 (ASH). Twenty four hour proteinuria, blood urea nitrogen (BUN), and serum creatinine (SCr) were detected. Hematoxylin–eosin (HE) and periodic acid‐Schiff (PAS) staining were performed to evaluate the kidney lesion. Transmission electron microscope and GFP‐RFP‐LC3 transfection assay were used to monitor the effect of AS‐IV on autophagy. IL‐6 and IL‐1β were detected. The expression of CyclinD1, PI3K/AKT/AS160 pathway and autophagy related proteins were detected by Western Blot. The results demonstrated that AS‐IV improved kidney function, ameliorated kidney lesion, and diminished inflammatory in CGN rats. Further, both in vivo and vitro study demonstrated that AS‐IV inhibited the proliferation of mesangial cells. AS‐IV further displayed a remarkable effect on inhibiting the activation of PI3K/AKT/AS160 pathway and improved the activation of autophagy in vivo and vitro. These results suggested that AS‐IV is a potential therapeutic agent for CGN and merits further investigation.